Follow-Up of Nonarteritic Anterior Ischemic Optic Neuropathy With Optical Coherence Tomography Angiography - Augstburger, Edouard (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: The purpose of this study was to describe capillary changes in patients with nonarteritic anterior ischemic optic neuropathy (NAION) using optical coherence tomography-angiography (OCT-A) and correlate the results with best corrected visual acuity (BCVA), visual field, OCT retinal nerve fiber layer (RNFL), and combined thickness of ganglion cell and inner plexiform layers (GCIPL) thicknesses. METHODS: We enrolled 22 eyes with acute NAION and 30 normal control (NC) subjects in this study. Whole en face image vessel density (WiVD) was measured in the radial peripapillary capillary plexus (RPC), superficial capillary plexus (SCP), and deep vascular complex (DVC) using OCT-A. The examination was repeated at 1 (M1), 3 (M3), 6 (M6), and 9 (M9) months after presentation for NAION. RESULTS: The initial RPC WiVD was significantly reduced in the acute NAION group compared to the NC group (P < 0.0001). Over the course of NAION follow-up, RPC WiVD was significantly reduced at M1 (P < 0.001 compared to M0) and M3 (P < 0.0001 compared to M1). However, there was no significant further decrease at M6 and M9. The initial SCP WiVD was significantly reduced in the NAION group compared to the NC group (P < 0.0001 for both). Over the course of NAION follow-up, a significant decrease was observed for SCP WiVD at M1 (P < 0.001 compared to M0), but no significant change was seen at M3, M6, or M9. DVC was normal in the NAION group. Correlations were found between GCIPL and SCP WiVD in the NAION acute phase (R = 0.604, P = 0.003) and in the M9 atrophic stage (R = 0.551, P = 0.009). At M9, RPC WiVD was correlated with BCVA (R = −0.562, P = 0.007), mean deviation (R = 0.518, P = 0.01), and RNFL (R = 0.655, P = 0.001). CONCLUSIONS: Over the course of NAION, OCT-A provided detailed visualization of retinal capillary plexus involvement.